(untitled) (Fiep Bulletin - online, 2011)
The aim of this study is to present the mapping done on the football on the internet. We tried to see how this theme which was recently incorporated into objects of study of humanities and social sciences has been analyzed and disseminated through the World Wide Web. After a preliminary survey, the approaches were divided into four distinct categories, but interdependent, because all have as a central approach to football, whether through scientific articles, websites, blogs or movies. It was felt that this is a theme that every day gained more adherents in the academic world and also on the big screen. However, what has been produced so far is still far from reaching the potential generator of this issue (be it in terms of academic or commercial), which at times has been used to define the culture and identity of the Brazilian.